Human amniotic fluid stem cell injection therapy for urethral sphincter regeneration in an animal model - Kim Bum; Chun So; Lee Jong; Lim Hyun; Bae Jae-sung; Chung Ho-Yun; Atala Anthony; Soker Shay; Yoo James J; Kwon Tae (BMC Medicine, 2012)
Abstract Background Stem cell injection therapies have been proposed to overcome the limited efficacy and adverse reactions of bulking agents. However, most have significant limitations, including painful procurement, requirement for anesthesia, donor site infection and a frequently low cell yield. Recently, human amniotic fluid stem cells (hAFSCs) have been proposed as an ideal cell therapy source. In this study, we investigated whether periurethral injection of hAFSCs can restore urethral sphincter competency in a mouse model. Methods Amniotic fluids were collected and harvested cells were analyzed for stem cell characteristics and in vitro myogenic differentiation potency. Mice underwent bilateral pudendal nerve transection to generate a stress urinary incontinence (SUI) model and received either periurethral injection of hAFSCs, periurethral injection of Plasma-Lyte (control group), or underwent a sham (normal control group). For in vivo cell tracking, cells were labeled with silica-coated magnetic nanoparticles containing rhodamine B isothiocyanate (MNPs@SiO2 (RITC)) and were injected into the urethral sphincter region (n = 9). Signals were detected by optical imaging. Leak point pressure and closing pressure were recorded serially after injection. Tumorigenicity of hAFSCs was evaluated by implanting hAFSCs into the subcapsular space of the kidney, followed two weeks later by retrieval and histologic analysis. Results Flow activated cell sorting showed that hAFSCs expressed mesenchymal stem cell (MSC) markers, but no hematopoietic stem cell markers. Induction of myogenic differentiation in the hAFSCs resulted in expression of PAX7 and MYOD at Day 3, and DYSTROPHIN at Day 7. The nanoparticle-labeled hAFSCs could be tracked in vivo with optical imaging for up to 10 days after injection. Four weeks after injection, the mean LPP and CP were significantly increased in the hAFSC-injected group compared with the control group. Nerve regeneration and neuromuscular junction formation of injected hAFSCs in vivo was confirmed with expression of neuronal markers and acetylcholine receptor. Injection of hAFSCs caused no in vivo host CD8 lymphocyte aggregation or tumor formation. Conclusions hAFSCs displayed MSC characteristics and could differentiate into cells of myogenic lineage. Periurethral injection of hAFSCs into an SUI animal model restored the urethral sphincter to apparently normal histology and function, in absence of immunogenicity and tumorigenicity.